توظيف دلالة الاسم (العلم) في النصِّ الشِّعريّ عندَ المتنبي / The Employment of the Connotation of the proper Noun in Al- Mutanabbi’s Poetic Text - Bashir Al-Tom Bashir, Al-Aṣsam; Ibrahim Muḥammad Ismail , Al-Tijani (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2021)
مُلخَّص البحث: تهدف هذه الدراسة إلى تتبُّعِ وُرُودِ الاسم العلم في شِعرِ المتنبي؛ لبيانِ مَدَى توظيف الشاعر للمعاني اللغوية لهذه الأعلام ودلالاتها في بناء أفكاره الشعرية داخل أبياته وقصائده. تكمن أهمية الدراسة في أنها تدرس ظاهرة إكثار المتنبي، في شعره، من إيراد أسماء مَمْدُوحِيهِ وألقابِهم وكُنِيِّهم، وغير ذلك من أسماء القبائل والأماكن، والمعاني العامّة، مستفيداً من ذلك في توسيع دائرة أفكاره معنًى ولفظاً وتركيباً. وقد سارت على خطا المنهج الوصفي التحليلي؛ حيث طرح الباحثان مجموعةً من الأسئلة، من ذلك: لماذا أكثر المتنبي من ذِكْرِ تلك الأسماء في ثنايا بعض قصائده؟ وهل اقتصر في ذلك على أسماء الأناسِيِّ فقط، أم زادَ وتوسَّعَ لِيشمل أسماء القبائل والأماكن وغيرها؟ وهل ساعدَه ذلك في استيفاء الأغراض الشعرية التي رَمَى إليها؟ وهل للوضع السياسيّ الذي أظلَّ الشاعرَ دورٌ في الالتفات إلى معاني بعض الألقاب؟ هذه الأسئلة وغيرها دفعت الباحِثَيْنِ إلى افتِرَاضِ وجود ظاهرةٍ في شعر المتنبي تتمَثَّلُ في (توظيف دلالة الأسماء الأعلام في نصوصه الشعرية)؛ أي أنّه وَظَّفَ معاني تلك الأسماء ودلالتها اللفظية توظيفاً حَسَناً في سياقات شعره المختلفة، وساعده ذلك في بناء تراكيب الجُمل والعبارات داخل نصوصه الشعرية؛ ما حَدَا بالباحِثَيْنِ إلى إفرادِ شعرِهِ بهذه الدراسة. ومن النتائج التي توَّجت هذا البحث استعمال المتنبي لمنهج المقارنة (المُقارَبَة) بين المعاني اللُّغوية وبين ما نُقلَ إليه من الأعلام لإبراز سِمات الممدوحِ أو ضَعَةِ المهجوِّ، وإنّ الربط بين الأصلِ اللغويِّ لدِلالة الاسم العلم وبين المعنى الذي يسوقه الشاعر في صياغة شعره، يسمو بفكرة النصِّ الشعري ويجعله أكثر تماسكاً وانسجاماً. الكلمات المفتاحية: لَقَب، كُنْيَة، توظِيف، المتنبي، سيف الدولة. Absract The present study aimed to trace the frequency of occurrence of the proper noun in the poetry of Al-Mutanabbi, to indicate the extent to which the poet has employed the linguistic meanings of these proper nouns and their connotations in the construction of his poetic thoughts as expressed in his poetry lines and poems. The importance of the study lies in that it seeks to examine the phenomenon of Al-Mutannabi’s frequent mentioning of the names of those he praised and their nicknames, as well as the names of tribes and places and general meanings, benefiting from that in broadening the circle of his thoughts in terms of meaning, connotation, and pronunciation. The study adopted the descriptive- analytic method. The two researchers have posed several questions such as: Why did Al-Mutanabbi frequently use these names in the folds of his poems? Did he restrict the use of proper nouns to the names of people or expand the use of proper nouns to include the names of tribes, places, etc.? Did that help him achieve his poetic purposes? Did the political situation under which the poet lived play any role in giving his attention to the meanings of some nicknames? These questions and others have motivated the two researchers to assume the existence of a phenomenon in the poetry of Al-Mutanabbi represented in (the employment of the meaning of the proper nouns in his poetic texts), that is, he has utilized the meanings of these names and their verbal connotations well in the different contexts of his poetry, which has helped him in the construction of sentences and expressions in his poetic texts. Among the results that the present study has come to is that he used the method of comparison between linguistic meanings and what was transmitted to him from the other literary figures to highlight the features of the praised, or the inferiority of satirized person, and the connection between the Linguistic origin of the proper noun’s meaning and the meaning postulated by the poet in his poetic diction elevates the idea of the poetic text and makes it more cohesive and harmonious. Keywords: Title, Nickname, employment, Al-Mutanabbī, Saif al-Dawla. Abstrak Kajian ini bertujuan untuk mengesan kekerapan kemunculan kata nama khas dalam puisi Al-Mutanabbi, untuk menunjukkan sejauh mana penyair tersebut telah menggunakan makna linguistik kata nama khas ini dan konotasinya dalam pembinaan pemikiran puitisnya sebagaimana yang diungkapkan dalam baris syairnya. Kepentingan kajian ini ialah untuk mengkaji stail Al-Mutannabi yang kerap menyebut nama-nama orang yang dipujinya dan nama panggilan mereka, serta nama kabilah mereka dan nama tempat tinggal mereka dan makna-makna umum yang lain. Ini adalah untuk mengeksploitasi makna-makna tersebut dalam meluaskan lingkaran pemikiran di dalam syairnya dari segi makna, konotasi, dan sebutan kata-kata nama tersebut. Kajian ini menggunakan kaedah deskriptif dan analitik. Kedua-dua pengkaji telah mengemukakan beberapa persoalan seperti: Mengapakah Al-Mutanabbi kerap menggunakan nama-nama ini dalam baris-baris syairnya? Adakah beliau membataskan penggunaan kata nama khas hanya kepada nama orang atau meluaskan penggunaannya untuk memasukkan nama suku kabilah, tempat tinggal mereka dan sebagainya? Adakah itu membantunya mencapai tujuan syairnya? Adakah situasi politik di mana seseorang penyair itu hidup memainkan peranan dalam menjadikannya memberikan perhatian kepada makna beberapa kata nama panggilan? Soalan-soalan ini dan lain-lainnya telah mendorong kedua-dua pengkaji untuk menganggap kewujudan fenomena dalam syair Al-Mutanabbi melalui penggunaan makna kata nama khas dalam teks puisinya, iaitu, beliau telah memanfaatkan maksud kata-kata nama ini dan konotasinya dengan baik dalam konteks syairnya yang berbeza. Ini telah membantunya dalam pembinaan ayat dan ungkapan dalam teks puisinya. Di antara rumusan yang diperoleh oleh kajian ini ialah beliau dilihat telah menggunakan kaedah perbandingan antara makna linguistik dan apa yang dimabil daripada daripada tokoh-tokoh syair lain untuk menonjolkan ciri-ciri orang yang dipuji, atau rendah diri orang yang disindir, dan kaitan di antara makna asal linguistik kata nama khas itu dengan makna yang didalilkan oleh penyair dalam diksi syairnya bertujuan untuk meningkatkan idea teks syairnya dan menjadikannya lebih kohesif dan harmoni. Kata kunci: Gelaran, Nama Panggilan, pekerjaan, Al-Mutanabbī, Saif al-Dawla.